(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The recreational assessment of hypsometric zones of the Northern Armenia relief (Shirak, Lori, Tavush) is given in the article. A large-scale map was drawn up for the study which shows not only hypsometric zones but also their recerational objects. And in order to assess the zones, an assessment scale was desinged.